(3TQM cJGH GdfabGJs - (3GdMfaj GdNQGSGfj, CHh eMeO, GdnqUrOQ GdnqTpgjO, HQgGf GdCFeI, YeQ Hf YHO GdYRjR Hf YeQ Hf eGRI, (B536 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; bGd QVj Gddg Yfg (B: (3LeY UGMH GdcJGH GdTjN GdEeGe CHh HcQ CMeO Hf YeQ GdNUGa QMeg Gddg aj gPG GdcJGH eSGFd GdfabI hLYdgG Ydi CbSGe s
(3BNQgG (B:s
(3Edi HGH GdeQCI JWdb hJQjO Cf JNQL HGdhdO aCQGOJ Cf Jfbdg Edi GdehVY GdPj hbY ajg YbO GdecGM adjS dgG Pdc dCf gPG Mb KHJ MceG ddfcGM ajchf KGHJG Hjf GdCe hGdRhL dG Hjf ZjQgeG hGddg CYde hCMces
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 51s
(3eYLe GdeDdajf (B2 / 562s
(3cTa GdXfhf (B2 / 1414s
(3GdLhGgQ GdeVjI (B1 / 391s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs